Connecting Countries by Electric Roads. Methodology for Feasibility Analysis of a Transnational ERS Corridor. - Jöhrens, Julius; Helms, Hinrich; Lambrecht, Udo; Spathelf, Felix; Mottschall, Moritz; Hacker, Florian; Jelica, Darijan; Alfredsson, Hampus; Gustavsson, Martin G.H.; Neubauer, Gregor; Schubert, Markus; Almestrand Linné, Philip; et al. (My University, 2021)
The present study aims at discussing relevant aspects for a potential roll-out of Electric Road Systems (ERS) on transnational corridors, as well as generally for ERS introduction in Europe.
Keywords: Elektromobilität; Fernstraßenplanung; Straßenverkehrstechnik; Verkehrstechnologie; Machbarkeitsstudie; Electric road system (ERS)